The crystal structure of 4-bromobenzyl chloride, C7H6BrCl - Manana Pholani; Hosten Eric C.; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures)
C7H6BrCl, orthorhombic, Pna21 (no. 33), a = 9.4506(7) Å, b = 18.1015(10) Å, c = 4.4418(3) Å, V = 759.86(9) Å3, Z = 4, Rgt(F) = 0.0271, wRref(F2) = 0.0558, T = 200(2) K.